The Distribution of Public Revenues in the municipalities of the State of Bahia: A Critical Analysis of its Equity - Lira, Neila Karolina Mendes; Monteiro, Augusto de Oliveira; Fadul, Élvia Mirian Cavalcanti (Organizações & Sociedade, 2013)
This paper aims to assess the degree of equilibrium in the distribution of revenuesamong municipalities of the State of Bahia and the effectiveness of its use inthe period of 1998 the 2006. In order to do so, it analyzed the distribution andcomposition of municipal revenues and identified its evolution. The demand ofservices was evaluated on the basis of the population. Then, the degree of equilibriumwas analyzed through the calculation of revenues per-capita of each municipality.Finally, effectiveness of public services was assessed by means of the Social DevelopmentIndex (SDI) and an analysis of correlation between the revenues per-capita andSDI. Results showed high disparity among municipal revenues, deriving from hugeintergovernmental transferences asymmetry, implying in a very low level of balancein the distribution of the public resources.